Methodological approaches and goal-setting for development of indicators of production manufacturability of orders and processes - L. K. Sirotina (Омский научный вестник)
The article is devoted to the problem of forming the necessary reference information about the generalized indicators of the production manufacturability of products, orders and processes based on the results of organizational preparation when planning the order-by-order production of small-scale products of textile and clothing enterprises. The development of the necessary background information on the indicators of material intensity and labor intensity of orders will allow to systematize the process of their comprehensive preparation and production planning, taking into account the existing organizational and technical conditions and efficiency requirements. The approaches, the purpose and objectives of calculation and the directions of evaluation of generalized indicators of production manufacturability of orders and processes for the needs of volume and calendar planning of production in the conditions of enterprises of the studied industry are described.